Pengaruh Pelaksanaan Program Takhassus Hafalan dan Pemanfaatan Sarana Prasarana Terhadap Prestasi Belajar Mata Pelajaran PAI Siswa - Ardila, Een; Alwi, Rohimin; Khoiri, Qolbi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the effect of the implementation of the memorizing takhassus program and the use of infrastructure on the learning achievement of fifth grade PAI subjects at the Al-Qiswah integrated Islamic elementary school, Bengkulu City. This type of research is a type of quantitative research data, quantitative is data in the form of numbers or qualitative data that is raised/scoring, with an ex post facto, ex post facto approach. The results of the study explain, 1) there is an effect of the implementation of the rote takhassus program on the learning achievement of fifth grade PAI subjects at the Al-Qiswah Integrated Islamic Elementary School Bengkulu City, which means Ha1 is accepted and Ho1 is rejected in this study, 2) there is an influence between the use of facilities infrastructure on learning achievement in children in PAI subjects for fifth grade students at Al-Qiswah Integrated Islamic Elementary School, Bengkulu City. In conclusion, there is an influence between the implementation of the memorizing takhassus program and the use of infrastructure on the learning achievement of the fifth grade PAI subject at the Al-Qiswah Integrated Islamic Elementary School Bengkulu City, which means Ha3 is accepted and Ho3 is rejected in this study. Keywords: Implementation of rote takhassus program, Infrastructure And Student Achievement.